What kind of goods are plant genetic resources for food and agriculture? Towards the identification and development of a new global commons. Issue 2 (August 2013) - Halewood, Michael
Plant genetic resources for food and agriculture (PGRFA) were once widely considered to be global public goods. Recently, however, access to subsets of PGRFA has been subject to various forms of exclusive technological and legal restrictions. In reaction, numerous voluntary pooling initiatives – from local to global scales – are being experimented with, in an attempt to re-strike a balance more supportive of agricultural research and development. The first part of the paper argues that different subsets of PGRFA can now be accurately described as public goods, private goods, club goods and common pool resources, but that these categories do not fully interrogate important 'exogenous variables' concerning PGRFA. As the products of complex interactions between crops breeding systems and natural and human selection, PGRFA occupy a middle ground between natural resources and human-make cultural resources. The paper identifies which subsets of PGRFA are (or could be) included in an evolving global plant genetic resources commons. The paper uses Elinor Ostrom's eight design principles for long enduring commons to analyze the extent to which the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA) supports this evolving global commons. The paper concludes by identifying options for policy reforms to provide better tailored institutional support for the plant genetic resources commons.